2020
DOI: 10.2174/1871520620666200516150829
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Flavonoids and Tannins from Medicinal Plants as Anticancer Agents

Abstract: : The tendency of using herbs extracts or natural compounds extracted from herbs for preventing or treating different illness, including cancer, continues to be an alternative to drug use. Many studies of plants compounds are aimed to find substances with selective cytotoxicity on abnormal cells. Phenolic compounds, as important secondary metabolites from plants are between them. In this review, the recent literature data from past five years about anticancer/antitumor effect of flavonoids and tannins extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 137 publications
0
20
0
Order By: Relevance
“…The already published results of research on potential pharmaceutical and medical applications of tannins point out to their positive effect on the functionality of intestinal as well as to anticancer, anti-inflammatory, anti-allergic or antiviral activity [ 43 , 50 , 51 , 56 , 64 , 65 , 66 , 67 , 68 , 69 ]. The specific properties of tannins that enable their irreversible binding to proteins make them also a useful weapon against microorganisms.…”
Section: Antifungal Substances Of Plant Originmentioning
confidence: 99%
“…The already published results of research on potential pharmaceutical and medical applications of tannins point out to their positive effect on the functionality of intestinal as well as to anticancer, anti-inflammatory, anti-allergic or antiviral activity [ 43 , 50 , 51 , 56 , 64 , 65 , 66 , 67 , 68 , 69 ]. The specific properties of tannins that enable their irreversible binding to proteins make them also a useful weapon against microorganisms.…”
Section: Antifungal Substances Of Plant Originmentioning
confidence: 99%
“…Meanwhile, 3 similar wood samples contained slight tannin compounds. These compounds are obtained from various plant extracts, which possess anti-cancer and anti-microbial properties [53,54]. Based on the results, the different lianas types used by the Kaili tribe were detected to contain tannin used as kidney, cancer, and tumor medicines.…”
Section: Taninmentioning
confidence: 99%
“…Although several studies have reported that relatively 1.5 to 23% are also found in plant roots, it is also found in leaves [58]. Saponin compounds in various medicinal plants have been globally proven to possess anti-cancer and other pharmacological properties [54,59].…”
Section: Saponinmentioning
confidence: 99%
“…Natural compounds and antioxidants are no exception, and are superior to synthetic compounds with their exceptionally broad activity [ 370 , 371 ]. A large number of these compounds are at various stages of clinical and preclinical research [ 365 , 372 ].…”
Section: Natural Compounds and Important Targets Associated With Chronic Inflammation And Oxidative Stress In Cancer Treatmentmentioning
confidence: 99%